Repensar a vocação oceânica da Ordem de Cristo (séculos XV e XVI) - Olival, Fernanda (2022)
This chapter questions the vocation of the Order of Christ to be involved in the process of oceanic exploration in the 15th century. Nor did it get institutionally involved in the conquest of squares in North Africa. The emergence of the patronage is explained by the rivalry between Portugal and Castile in the mid-15th century. It is noted that the Order of Christ did not even have clerics to ensure evangelisation at that time.